Strength and Stiffness Degradation Mechanisms of Stabilized/Solidified Sediments by Freeze–Thaw Cycles - Wang, Hongxing; Wu, Shangwei; Jing, Xiaofei; Liu, Kehui; Ren, Lingyan (Frontiers in Earth Science, 2022)
Strength and stiffness of Stabilized/Solidified (S/S) sediments are supposed to be degraded by freeze-thaw cycles (FTs) when applied in constructions in cold regions. In order to reveal the degradation mechanisms, FTs were first simulated on S/S sediments in laboratory. Then, macro tests including unconfined compression strength (UCS) tests and direct shear tests were conducted on S/S sediments at different FTs to investigate the strength and stiffness changes, and micro analyses including scanning electron microscope analysis (SEM), mercury intrusion porosimetry (MIP) and nitrogen adsorption porosimetry (NAP) to investigate the microstructure changes. Macro tests show that strength indexes decrease gradually, stiffness parameters and brittleness increase first and then decrease, compaction stage of stress-strain curves diminishes first and then increases, decrease rate of friction angel decelerates first and then accelerates, decrease rate of cohesion decelerates first and then keeps stable, for S/S sediments in FTs. Micro analyses have precisely captured the damage chain of S/S sediments: meso and macro pores inside sediment aggregates expand gradually during FTs; as a result, sediment aggregates are fractured and stripped off from solidification skeleton gradually; losing support of sediment aggregates, solidification skeletons are adjusted first, and then collapsed when sediment aggregate fracture reaches a limit value. Based on macro and micro findings, a damage model to explain strength and stiffness degradations by microstructure damage is successfully established. Based on the established damage model, reasonable idea is proposed for promoting resistance of S/S sediments to FTs.